THE PAIN THAT TRAVELS: A COMPREHENSIVE REVIEW OF REFERRED PAIN - Asatullyev Rustam Baxtiyorovich; Asherbekova Rayhon Kalilbek qizi (TADQIQOTLAR, 2026)
Abstract: Referred pain is a fascinating and clinically significant phenomenon in which pain is perceived at a location distant from its actual source of origin. This neurophysiological phenomenon poses a substantial diagnostic challenge for clinicians, as the site of discomfort often does not correspond to the underlying pathological process. Common examples include cardiac ischemia presenting as left shoulder or jaw pain (angina pectoris), diaphragmatic irritation causing shoulder tip pain, and lumbar disc herniation producing sciatic pain radiating down the lower extremity. This article provides a systematic review of the historical understanding, neuroanatomical basis, and leading theories of referred pain, including the convergence-projection theory, the facilitation theory, and the axonal branching theory. The clinical relevance of referred pain is explored across multiple medical specialties, including cardiology, gastroenterology, pulmonology, orthopedics, and neurology. The article also discusses diagnostic approaches, including the use of local anesthetic blocks and imaging, and outlines management strategies. The review concludes with a discussion of the clinical red flags (e.g., sinister causes of referred pain such as aortic dissection or pancreatic cancer) and future research directions, including central sensitization and neuroimaging studies.